Advances in preparation and application of coal-based functional nanomaterials - Shenyong LI; Shenjun QIN; Changquan MEN; Jiajia HOU; Dawei LYU; Xue ZHENG; Wei PANG; Longlong HAO; Daoyuan ZHAO; Shaozhuo ZHANG (Meitan xuebao)
China’s energy resource endowment, characterized by “abundant coal but scarce oil”, establishes coal’s fundamental role in the national energy system. However, traditional coal utilization as a primary carbon emission source fundamentally conflicts with the “dual-carbon” strategic goals. Achieving low-carbon transformation of high-carbon resources through clean and efficient coal utilization represents both a practical requirement for energy security and a strategic pathway for fostering new productive forces. Nanomaterials demonstrate unique advantages in electronics, new energy, biomedicine, and environmental remediation due to their quantum effects and surface characteristics. The polycyclic aromatic hydrocarbon networks in coal’s organic matter and inorganic components like aluminosilicates provide structural units for functional materials: The former can be transformed into zero-dimensional carbon quantum dots, two-dimensional graphene, and carbon nanotubes through directed carbon rearrangement, while the latter can be reconstructed into nanoporous systems such as zeolites and mesoporous materials. Notably, the “carbon-ash composites” containing unburned carbon and inorganic ash present novel opportunities for functional material design. This paper systematically analyzes the structure-property regulation mechanisms of coal-based nanomaterials, revealing that the dimensionality of carbon nanomaterials is primarily governed by coal metamorphic grade. It provides a comprehensive review of preparation technologies for coal-derived nanomaterials and their applications in lithium battery anodes, electrocatalysis, and pollutant detection. Furthermore, the study elucidates the phase evolution mechanisms of silicon-aluminum components in coal-based solid waste and their conversion into nanoporous materials, while exploring their potential in CO2 capture and heavy metal adsorption. Current challenges include product inconsistency caused by feedstock heterogeneity and environmental risks from acid/alkali treatment processes. Future research should prioritize precise structural analysis at the molecular scale, synergistic conversion of multi-source solid wastes, and development of green preparation technologies. With the advancement of “raw material substitution” strategies and nanotechnology innovations, coal-based nanomaterials are poised to emerge as a value-added utilization pathway, offering scientific support for building a clean coal-based materials industry system.